The Redundancy Effect on Retention and Transfer for Individuals with High Symptoms of ADHD - Brown, Victoria; Lewis, David; Toussaint, Mario (Journal of the American Academy of Special Education Professionals, 2016)
The multimedia elements of text and audio need to be carefully integrated together to maximize the impact of those elements for learning in a multimedia environment. Redundancy information presented through audio and visual channels can inhibit learning for individuals diagnosed with ADHD, who may experience challenges in the processing of information through visuospatial and phonological loop channels in the memory system. This study explores how redundancy affects the individuals with self-reported higher levels of ADHD symptoms ability to process information presented using multimedia presentations. Individuals with higher-reported ADHD symptoms had lower performance levels when using the multimedia presentation with redundancy.